ENLIGHTENED IDEAS FOR MODERN PEACE EDUCATION. FROM KANT TO HUMBOLDT - BACHER, Sabrina Viktoria; KRALER, Christian; BINYTSKA, Kateryna (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2024)
Abstract. Amidst a backdrop of global conflict, particularly exemplified by Russia’s invasion of Ukraine, peace education emerges as a key element for fostering a culture of peace and conflict resolution. This paper examines the concept of peace education by linking it to some of its philosophical foundations, particularly drawing from the Enlightenment and Neo-Humanism movements. It explores the philosophical underpinnings of peace education through the lenses of Immanuel Kant (1724-1804) and Wilhelm von Humboldt (1767-1835) by reconstructing their insights into education’s role in fostering a peaceful co-existence of humanity. By leveraging these philosophical foundations, Ukraine has the potential to nurture a culture of long-lasting peace that transcends the immediate aftermath of the war, not only within its borders but also as a model for global peacebuilding efforts. The insights drawn from the philosophical foundations of peace education underscore the critical role of education in fostering a peaceful society. Kant’s emphasis on cultivating rationality, moral autonomy, and a cosmopolitan worldview, alongside Humboldt’s advocacy for self-realization, holistic development, and cultural appreciation provide a robust framework of values that are essential for contemporary peace education. Both philosophers highlight the transformative potential of education in shaping individuals who are not only knowledgeable but also morally and socially responsible. In accordance with Kant and Humboldt, peace education serves as a transformative force that empowers individuals towards autonomy, upholds human dignity, and fosters moral and intellectual growth. By nurturing these values within individuals and communities, peace education lays the foundation for a more just, peaceful, and inclusive society. In the midst of war, Ukraine has the opportunity to strengthen values, such as rationality, moral autonomy, holistic development, and cultural appreciation, which are fundamental components of peace education, rooted in the philosophies of Kant and Humboldt. By prioritizing these principles, Ukraine can foster a young generation who is not only knowledgeable but also equipped with the empathy, tolerance, critical thinking, and commitment to justice needed for a peaceful society. As Ukraine rebuilds, it is crucial to maintain a concerted focus on peace education, ensuring that it remains a central pillar in the nation’s reconstruction strategy. This holistic approach, which combines the strengths of peace education with human rights education, can help create a more peaceful and equitable world. The journey towards sustainable peace is challenging, but with dedicated efforts and a robust educational framework, Ukraine can pave the way for a brighter and more peaceful future for its citizens and inspire similar transformations globally.